Corticosteroid therapy augments gastroduodenal permeability to sucrose - (:unkn) unknown (My University, 1998)
Objective: The aim of the present study was to investigate whether corticosteroid therapy alters gastroduodenal mucosal permeability and whether permeability alteration is associated with macroscopic mucosal damage. Methods: Eight patients taking oral corticosteroid therapy (total prednisone- equivalent dose, 1.5 ± 0.1 g; duration, ~30 days), nine patients with multiple sclerosis taking high-dose intravenous methyl-prednisolone therapy (total dose, 11.7 ± 0.5 g; duration, ~9 days), and 20 age- and gender- matched controls were studied. Gastroduodenal permeability was determined using sucrose as a site-specific permeability probe. Five-hour urine was collected after ingesting 100 g of sucrose and its urinary excretion rate was measured using high-pressure liquid chromatography. Gastroduodenal endoscopy was performed before steroid therapy to exclude subjects with evidence of macroscopic mucosal lesions. The sucrose test and endoscopy were repeated after completion of corticosteroid therapy. Results: The urinary sucrose excretion rates were similar in the control group and in patient groups before corticosteroid therapy. The median excretion rate of sucrose increased four (one to 28)- and eight (two to 35)-fold, respectively, as compared with pretreatment values in patients taking oral steroid and high-dose intravenous methyl-prednisolone therapy (p < 0.01). Considering all patients together, subjects who received a mean prednisone-equivalent dose of 8.4 ± 1.5 g exhibited mucosal lesions, whereas patients who received 3.3 ± 1.8 g did not (p = 0.06). The posttherapy increments in sucrose excretion rates were associated with neither the presence of macroscopic lesions nor with the total steroid dose received. Conclusions: Corticosteroid therapy augments gastroduodenal permeability and high doses are associated with macroscopic mucosal lesions. Steroid-induced permeability increase does not appear to be associated with the presence of macroscopic mucosal lesions.